Robust observer-based passive control for uncertain singular time-delay systems subject to actuator saturation - Ma, Yuechao; Yang, Pingjing; Yan, Yifang; Zhang, Qingling (ISA transactions, 2017)
This paper investigates the problem of robust observer-based passive control for uncertain singular time-delay system subject to actuator saturation. A polytopic approach is used to describe the saturation behavior. First, by constructing Lyapunov-Krasovskii functional, a less conservative sufficient condition is obtained which guarantees that the closed-loop system is regular, impulse free, stable and robust strictly passive. Then, with this condition, the design method of state feedback controller and the observer are given by solving linear matrix inequalities. In addition, a domain of attraction in which the admissible initial states are ensured to converge asymptotically to the origin is solved as a convex optimization problem. Finally, some simulations are provided to demonstrate the effectiveness and superiority of the proposed method. •The robust observer-based passive control problem for uncertain singular time-delay system subject to actuator saturation is investigated, which has not been reported in the literature.•Using Lyapunov-Krasovskii function method, the design of state observer feedback controller is given by solving LMIs.•A domain of attraction in which the admissible initial states are ensured to converge asymptotically to the origin is solved as convex optimization problem.•The condition derived in this paper is less conservative than some reports in the literature.